2012
DOI: 10.1159/000337780
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Medical Follow-Up of Young Women with Turner Syndrome Treated in One Clinical Center

Abstract: For Turner syndrome (TS) patients, smooth transition from pediatric to adult health care is a critical point. The study objective was to evaluate the medical follow-up of young women with TS in one clinical center 3 years after the latest guidelines had been introduced by the TS Study Group. A questionnaire study was performed in 59 TS adults selected from a database of 117 patients. Twenty-two of them, aged 23.0 ± 2.8 years, consented to participate. Nineteen responders (86.4%) were followed up by general pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
1
25
0
6
Order By: Relevance
“…The chances for a successful transition are decreased in some chronic conditions, including TS, because it is difficult to find experts in adult care (81). Young women with TS are furthermore seldom fully aware of their conditions (82, 83). In adult life, less than 4% of patients with TS undergo all the recommended medical investigations on a regular basis (84).…”
Section: Health Autonomy and Transitionmentioning
confidence: 99%
“…The chances for a successful transition are decreased in some chronic conditions, including TS, because it is difficult to find experts in adult care (81). Young women with TS are furthermore seldom fully aware of their conditions (82, 83). In adult life, less than 4% of patients with TS undergo all the recommended medical investigations on a regular basis (84).…”
Section: Health Autonomy and Transitionmentioning
confidence: 99%
“…It is recommended that women with TS should receive oestrogen and progestin replacement, known to have long-term effects on puberty, fertility, metabolism, and psychological functioning [4,5]. However, patient compliance with treatment is often variable, especially during late adolescence, when transition to adult care is being planned [6]. The international consensus is to initiate oestrogen therapy at the age of 12 years in the absence of spontaneous puberty and if follicle-stimulating hormone (FSH) levels are elevated.…”
Section: Prediction Of Spontaneous Puberty Inmentioning
confidence: 99%
“…Both clinical (78,80,122) and questionnaire studies (118,119) revealed that cardiovascular monitoring for TS was insufficient. All girls and women with TS require comprehensive cardiovascular evaluation to diagnose congenital heart diseases and hypertension and to exclude long-term consequences of childhood GH treatment on aortic structures or function.…”
Section: Cardiovascular Abnormalities In Transitionmentioning
confidence: 99%
“…According to a French study, blood glucose was one of the most common medical follow-up assessments in the young population (118). By contrast, screening for celiac disease by measuring tissue tTg IgA antibodies was the least common test (119). (93,95).…”
Section: Autoimmune Diseases During Transitionmentioning
confidence: 99%